Linha de costa e faixa de proteção à erosão costeira: estudo de caso nas praias do Saco, do Abaís e da Caueira, sul de Sergipe - Santos, João Paulo da Silva (2019)
The southern shoreline of Sergipe, bounded north and south by the Vaza Barris and Piauí/Real river mouths, shows erosion, accumulation or stability behavior. Some coastal erosion events caused damage to anthropic structures. Coastal protection methods, such as setback lines that require shoreline change rate data, are suggested in areas of shoreline retreat. Thus, this work aims to identify the shoreline behavior and to verify the efficiency of setback lines on the Saco, Abaís and Caueira beaches, southern of Sergipe. The methodology consisted of: (i) multitemporal analysis of the shoreline (1971 to 2017) using satellite images and aerial photographs, (ii) calculation of shoreline change rate and envelope, (iii) analysis of ebb tidal delta and shoreline morphology located at the Piauí/Real rivers mouth, and (iv) efficiency analysis of the setback lines by two different methods: fixed width of 33 m (method 1) and, width obtained by shoreline change rate and construction type (method 2). These setbacks, marked on the back of 1971 shoreline, were compared to the 2017 shoreline. In the period investigated, the shoreline change rate of Saco, Abaís and Caueira beaches were - 14.8 to +13.6 m/year, -0.15 to +2.02 m/year and -0.37 to -2.44 m/year, respectively. The envelope variation values ranged from 57 to 409 m for the Saco beach; 19 to 95 m for Abaís and 22 to 125 m for Caueira beach. The greatest value of the envelope for the Saco beach reflected the high morphological variability on shorelines contiguous to river mouths. The investigated beaches presented accretion, stability, erosion and extreme erosion behavior. The combined analysis of ebb tidal deltas and shoreline morphology corroborated the influence of the delta dynamics on the Saco beach shoreline configuration. The worst erosive scenario occurred, and still occurs, on the Saco beach, which presented sectors with extreme erosion. The causes of erosive events are diverse and associated with negative sediment budget. The setback line width of method 1 would have prevented damage to anthropic structures on the Abaís and Caueira beaches, but it would not have been enough in the southern sector of the Saco beach. On the other hand, method 2 showed values less than 33 m only on the Abaís beach. Thus, if setback lines (method 2) had been implemented in 1971, many of the anthropic structures damages would have been prevented. In this way, the data of this paper serve as subsidies to the environmental planning of the study area.